Calcium Sulfate with Plasma Rich in Growth Factors (PRGF) as Bone Substitute in the Treatment of Periapical Cyst: Case Report - Peñaloza-Cuevas DDS MSc PhD, R.; Mendiburu-Zavala DDS MSc PhD, C.; Cárdenas-Erosa DDS MSc, R.; Flores-Pineda Br, AG.; López-Medina Br, BA. (Odovtos - International Journal of Dental Sciences, 2016)
Introduction. Periapical cysts are preceded by a chronic periapical granuloma and stimulation of cell rests of Malassez present in the periodontal membrane. Usually, they are asymptomatic and are discovered incidentally during x-ray exams. On the other hand, when removed they leave a cavity that would take long to regenerate and could leave bone defects affecting implant rehabilitation. The use of calcium sulphate as bone graft its justified by its high biocompatibility and its ability to combine with phosphates to form apatite which stimulates osteogenesis. When combined with growth factors in platelet rich plasma, those factors will be released and will also stimulate osteoblast production. Case presentation. Male patient of 57 years comes for extraction of multiple dental organs. Clinically, remnants of preparations for fixed prostheses are observed, pale pink mucosa, at the level of dental organ 1.3, a radicular rest was observed. In panoramic radiography, a radiolucent area of approx. 1.5 cm in diameter with well-defined edges was observed. Discussion. The protocols to accelerate bone regeneration promote the conservation of bone architecture. The majority of patients that attend this institution and require this type of treatment are of low socioeconomic status, reason why calcium sulphate is suggested as bone graft because of its low cost and accessibility.